TERRITORIAL DISPUTES IN SOUTH CHINA SEA IN THE XXI CENTURY: EVOLUTION OF PARTICIPANTS’ POSITIONS - S. V. Novoseltsev (Сравнительная политика)
Territorial disputes in the South China Sea can be considered as one of the key conflictogenetic elements inSouth East Asiaand Asia Pacific Region. The existence of unsolved territorial disputes itself has a significant impact on the East Asian regional sub-system of international relations. Close economic interconnection betweenChinaand the regional countries, whichBeijingtries to use as a political instrument, makes the situation even more complicated. The article contains a brief analysis of the current condition of the long-standing conflict inSouth China sea, as well as its influence on the region and political processes in regional countries. The emphasis is made on the most important arguments of the involved parties and the evolution of their positions. A possibility for other states to join the conflict is also analyzed.